Analysis Performance Study Program Lecturer Education Language Indonesia FKIP HKBP University Nommensen Pematangsiantar - Dika Kristina Lambok Manurung; Septinar Silalahi; Mastiur verawaty Silalahi; Masni Veronika Situmorang (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
The focus of this study is to determine student satisfaction with lecturer performance in the learning process at the Faculty of Teacher Training and Education, Nommensen University, in Siantar City. All students in the Indonesian Language Education Study Program are the subjects of this study. Students in the Indonesian Language Education Study Program in the second semester of the 2024/2025 academic year are the subjects of this study. This study uses a questionnaire given to students. This study uses a quantitative approach and collects data through the distribution of questionnaires to students. The results of the study indicate that the level of student satisfaction with teacher performance is rated as good. In addition, the level of student satisfaction with teacher performance shows that students are satisfied with teacher performance in various aspects and components involved in the lecture process.